Strengthening Consumer Protection Through Digitalization of Monitoring Results of Water Quality Standards for Swimming Pools, Solus Per Aqua, and Malls - Saleh, Putu Samawati; Flambonita, Suci; Zakaria, Nashriana (Trunojoyo Madura University, 2025)
Quality standards for water health requirements for sanitation hygiene, swimming pools, solus per aqua (SPA), and malls monitor by the Public Health office. Still, the monitoring process has yet to publish. It has not provided legalization, such as labels or signs that consumers can recognize, even though information and legalization need as an effort to protect consumer rights, especially a guarantee of security and comfort when using or utilizing products from business actors. This article used an empirical study to describe the urgency of the publication and labeling of water quality standards for swimming pools, spas, and mall sanitation. The data were by polling managers of five swimming pools, ten spas, five malls, and 100 consumers as respondents. The research results are described in a qualitative descriptive manner based on primary and secondary data through a statutory approach and a legal sociology approach by prioritizing the fulfillment of transparent consumer services. The addition of benefits resulting from the supervision of water quality standards on the website of the Public Health office is one solution to strengthen consumer protection and, at the same time, become evidence of enhancing the state's role as a supervisor.